Local legislatures in small Russian cities: professionalism of deputies and efficiency of representative body of local government - Vitkovskaya, T.B. (Perm Federal Research Centre Journal, 2019)
The article attempts to analyze the issue of professionalism of deputies working within representative bodies of local government in small Russian cities. The duties of deputies as elected officials and representatives of public authority system are considered. The main tasks for deputies are highlighted, as well as knowledge and skills that a deputy should fulfill. The main problems to which low competencY of deputies can lead are indicated. Conclusions concerning the impact of education and professional experience on the effectiveness of parliamentary activity are made. The situation of corporate representation, when elected deputies are not motivated to work as a part of public urban authority system, is described. The article is based on the analysis of materials from a number of small cities in Sverdlovskaya oblast and Perm region.